1996
DOI: 10.1073/pnas.93.19.10457
|View full text |Cite
|
Sign up to set email alerts
|

Long-term potentiation increases tyrosine phosphorylation of the N-methyl-D-aspartate receptor subunit 2B in rat dentate gyrus in vivo.

Abstract: Long-term potentiation (LTP) is a form of synaptic memory that may subserve developmental and behavioral plasticity. An intensively investigated form of LTP is dependent upon N-methyl-D-aspartate (NMDA) receptors and can be elicited in the dentate gyrus and hippocampal CAI. Induction of this type of LTP is triggered by influx of Ca2+ through activated NMDA receptors, but the downstream mechanisms of induction, and even more so of LTP maintenance, remain controversial. It has been reported that the function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
112
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(114 citation statements)
references
References 39 publications
1
112
0
Order By: Relevance
“…We demonstrated that both the tyrosine phosphorylation of NMDAR«2 and the binding of p85 to NMDAR«2 were decreased in Fyn-de®cient mice. Because the level of tyrosine phosphorylation of NMDAR«2 is increased in LTP and taste learning (Rosenblum et al 1996;Rostas et al 1996;Rosenblum et al 1997), it is possible that the decreases of both tyrosine phosphorylation of NMDAR«2 and amounts of p85 bound to NMDAR«2 in Fyn-de®cient mice could be at least in part responsible for impaired LTP. Interestingly, Src family kinases could increase the activity of NMDARz1-NMDAR«1 channels but not of NMDARz1-NMDAR«2 channels (Kohr & Seeburg 1996).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that both the tyrosine phosphorylation of NMDAR«2 and the binding of p85 to NMDAR«2 were decreased in Fyn-de®cient mice. Because the level of tyrosine phosphorylation of NMDAR«2 is increased in LTP and taste learning (Rosenblum et al 1996;Rostas et al 1996;Rosenblum et al 1997), it is possible that the decreases of both tyrosine phosphorylation of NMDAR«2 and amounts of p85 bound to NMDAR«2 in Fyn-de®cient mice could be at least in part responsible for impaired LTP. Interestingly, Src family kinases could increase the activity of NMDARz1-NMDAR«1 channels but not of NMDARz1-NMDAR«2 channels (Kohr & Seeburg 1996).…”
Section: Discussionmentioning
confidence: 99%
“…LTP-inducing tetanic stimulation increases tyrosine phosphorylation of the GluN2B subunit of the NMDAR in the hippocampus 52,53 . Here we found that TBS caused an increase in GluN2B tyrosine phosphorylation that depended on Src (Fig.…”
Section: Nrg1β Did Not Alter the Level Of Src Within The Nmdar Complementioning
confidence: 99%
“…NMDA receptor-mediated currents are potentiated by Src-family tyrosine kinases and suppressed by tyrosine phosphatases (23,24). In addition, taste-learning increases tyrosine phosphorylation of GluR⑀2 in the rat insular cortex, and tyrosine phosphorylation of GluR⑀2 is increased after induction of LTP in the dentate gyrus of anesthetized adult rats (25)(26)(27). It is reported that Src and Fyn do not potentiate the current through recombinant GluR1-GluR⑀2 channels in 293 cells (28).…”
mentioning
confidence: 99%